Laboratory evidence of disseminated intravascular coagulation is associated with a fatal outcome in children with cerebral malaria despite an absence of clinically evident thrombosis or bleeding. (27th August 2015) - Moxon, C. A.; Chisala, N. V.; Mzikamanda, R.; MacCormick, I.; Harding, S.; Downey, C.; Molyneux, M.; Seydel, K. B.; Taylor, T. E.; Heyderman, R. S.; Toh, C.‐H.
Summary Background A procoagulant state is implicated in cerebral malaria (CM) pathogenesis, but whether disseminated intravascular coagulation (DIC) is present or associated with a fatal outcome is unclear. Objectives To determine the frequency of overt DIC, according to ISTH criteria, in children with fatal and non‐fatal CM. Methods/patients Malawian children were recruited into a prospective cohort study in the following diagnostic groups: retinopathy‐positive CM (n = 140), retinopathy‐negative CM (n = 36), non‐malarial coma (n = 14), uncomplicated malaria (UM), (n = 91), mild non‐malarial febrile illness (n = 85), and healthy controls (n = 36). Assays in the ISTH DIC criteria were performed, and three fibrin‐related markers, i.e. protein C, antithrombin, and soluble thrombomodulin, were measured. Results and conclusions Data enabling assignment of the presence or absence of 'overt DIC' were available for 98 of 140 children with retinopathy‐positive CM. Overt DIC was present in 19 (19%), and was associated with a fatal outcome (odds ratio [OR] 3.068; 95% confidence interval [CI] 1.085–8.609; P = 0.035]. The levels of the three fibrin‐related markers and soluble thrombomodulin were higher in CM patients than in UM patients (all P < 0.001). The mean fibrin degradation product level was higher in fatal CM patients (71.3 μg mL−1 [95% CI 49.0–93.6]) than in non‐fatal CM patients (48.0 μg mL−1 [95% CI 37.7–58.2]; P = 0.032), but, in multivariate logistic regression, thrombomodulin was the only coagulation‐related marker that was independently associated with a fatal outcome (OR 1.084 for each ng mL−1 increase [95% CI 1.017–1.156]; P = 0.014). Despite these laboratory derangements, no child in the study had clinically evident bleeding or thrombosis. An overt DIC score and high thrombomodulin levels are associated with a fatal outcome in CM, but infrequently indicate a consumptive coagulopathy.